1999
DOI: 10.1038/sj.bmt.1702024
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis and treatment of chemo- and radiotherapy-induced oral mucositis – are there new strategies?

Abstract: Summary:Oral mucositis is a major dose-limiting toxic effect of intensive cancer chemotherapy. Oral complications may lead to dose reduction or delay in further cancer treatment. Mucositis can be caused directly by cytotoxic effects and indirectly by sustained neutropenia after cytostatic therapy. An impaired mucosal barrier predisposes to life-threatening septic complications during aplasia. The prevalence of an oral focus in febrile neutropenia has been reported in up to 30% of cases and also reduces quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 140 publications
(142 reference statements)
2
57
0
1
Order By: Relevance
“…8,30 Although the patients in our study who had fever preprocedure had a higher rate of CAI, this difference did not reach statistical significance, in agreement with published literature. 2 Poor nutritional status has a known association with hematologic abnormalities 31,32 and puts patients at a greater risk of chemotherapy-induced neutropenia. 10 In addition, it has a negative impact on wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…8,30 Although the patients in our study who had fever preprocedure had a higher rate of CAI, this difference did not reach statistical significance, in agreement with published literature. 2 Poor nutritional status has a known association with hematologic abnormalities 31,32 and puts patients at a greater risk of chemotherapy-induced neutropenia. 10 In addition, it has a negative impact on wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…We have structured our manuscript-based thesis as follows: [6,[116][117][118]. Studies suggested the stages of progression of RIOM as initial hyperemia and erythema during the pre-ulcer phase where there is release of various pro-inflammatory cytokines from epithelial, vascular, and connective tissue cells at the site of tissue injury.…”
Section: Outlinementioning
confidence: 99%
“…Common potentially severe side-effects related to 5-FU include diarrhea, mucositis/stomatitis [3], and leucopenia [4]. Cardiotoxicity is a relatively uncommon sideeffect of 5-fluorouracil and capecitabine.…”
Section: Introductionmentioning
confidence: 99%